Randomized Trial to Evaluate Cardiometabolic and Endothelial Function in Patients with Plasma HIV-1 RNA Suppression Switching to Darunavir/Ritonavir with or without Nucleoside Analogues. Issue 4 (July 2013) - Guaraldi, G.; Zona, S.; Cossarizza, A.; Vernacotola, L.; Carli, F.; Lattanzi, A.; Beghetto, B.; Orlando, G.; De Biasi, S.; Termini, R.; Garau, M.
Abstract : Background: We performed a study to evaluate change in cardiometabolic and endothelial function in HIV-infected patients switching to darunavir/ritonavir (DRV/r) monotherapy versus triple therapy.Methods: The MONARCH trial recruited 30 patients who were taking triple combination therapy and with HIV RNA<40 copies/ mL. Patients were randomized to either DRV/r 800/100 mg once daily (OD) monotherapy or DRV/r 800/100 mg OD plus 2 nucleoside reverse transcriptase inhibitors (NRTIs). The primary objective was to assess endothelial function change from baseline to 24 and 48 weeks in brachial artery flow-mediated dilation (FMD) test; changes in endothelial precursor cells (EPCs) and circulating endothelial cells (CECs) were secondary objectives.Results: At baseline, the median age of participants was 43 years, 77% were men, and median CD4 cell count was 585 cells/μL. The median FMD (%) decreased in both arms in the study period ( P > .05), with no statistically significant difference between arms (10.7% at baseline and 6.7% at week 48 in the DRV/r + 2 NRTIs arm; 11.1% at baseline and 8.8% at week 48 in the DRV/r arm). The changes at week 48 were similar in the 2 arms for EPCs and CECs. Total cholesterol and low-density lipoprotein (LDL) cholesterol showed larger rises to week 48 in the DRV/r arm monotherapy group than in the triple-therapy group (+26 vs +9 mg/dL for total cholesterol and +14 vs +5 mg/dL for LDL cholesterol).Conclusions: In the MONARCH trial, switching from triple combination treatment to DRV/r, with or without nucleoside analogues, did not translate into clinically meaningful reductions in endothelial function as measured by FMD.